A study on visual communication kinder soaps packaging design / Wan Nurfathirah Haini Wan Noraziman - Wan Noraziman, Wan Nurfathirah Haini (2022)
Packaging is one of the most essential marketing tools available today. Packaging has evolved into a critical marketing tool in today's world, as a result of increased consumer social awareness and a focus on customer pleasure. The topic of this research was "A Study on Visual Communication Kinder Soaps Packaging Design". The study's goal is to look at the function of product and brand awareness in stimulating consumers' interest. Examining the product impact on the packaging design's overall appearance. To assess customer purchasing in visual communication. Most marketers rely on verbal communication to sell their products. On the other hand, mostly the packaging design needs a visual approach. Packaging is frequently the final step in a long communication chain that uses several channels. Advertising helps to market a product and get people into retailers. Packaging is the only physical point of interaction between customers. Packaging has the ultimate word when it comes to persuading potential clients. The importance of the main color scheme, graphics, symbols, and typefaces. When these components are integrated, they produce a powerful element in visual impression. This visual design will provide an advantage that may be used to create a distinctive package communication hierarchy. Consumers will recognize a package based on its form or a mix of the brand's color. Packaging design and visual communication in visual parts of the brand require continual development. As a result, the interaction between packaging design and visual communication is the key to product success in terms of customer decision-making.